Pengaruh Lingkungan Sosial Terhadap Self-Regulated Learning Siswa - I Nyoman Paska, Paskalis Edwin; Laka, Laurensius (SAPA - Jurnal Kateketik dan Pastoral, 2020)
English: The final outcome of a catechesis is determined not only by the content and learning method but also by the attitude of the students who accept it, including whether the student has self-regulated learning (SRL). The relationship between self-regulated learning (SRL) and learning achievement has been widely revealed in previous studies, but how the influence of the social environment to the SRL strategy of SMK students in Indonesia, still leaves a question. This study was made to determine whether there is an effect of parental involvement, peer support, and teacher support on students' SRL strategy in SMK Bhakti. This quantitative research takes data using probability sampling techniques, with the stratified random sampling method. Data analysis used Structural Equation Modeling (SEM) variance-based, namely Partial Least Squares (PLS-SEM), considering that there are variables with reflective and formative indicators in one research model. The findings of this study indicate that simultaneously Parental Involvement, Peer Support, and Teacher Support are significant predictors of SRL Strategy. In addition, partially, the three exogenous variables (Parental Involvement, Peer Support, and Teacher Support), each of them also shows a significant influence on SRL Strategy. Teacher support made the largest contribution, followed by Peer Support, and Parental Involvement as the smallest contributors. Catechists need to realize the importance of growing SRL for the students when doing catechesis. Indonesia: Hasil akhir sebuah katekese ditentukan bukan saja oleh isi dan metode pembelajarannya melainkan juga oleh sikap siswa yang menerimanya, antara lain apakah siswa tersebut memiliki self-regulated learning (SRL). Hubungan antara self-regulated learning (SRL) dan prestasi belajar telah banyak diungkap dalam penelitian-penelitian terdahulu, tetapi seperti apakah pengaruh lingkungan sosial terhadap strategi SRL siswa SMK, di Indonesia, masih menyisakan tanda tanya. Penelitian ini dibuat untuk mengetahui apakah terdapat pengaruh Keterlibatan Orang tua, Dukungan Teman Sebaya, dan Dukungan Guru terhadap Strategi SRL siswa di Sekolah Menengah Kejuruan (SMK) Bhakti Luhur. Penelitian kuantitatif ini mengambil data dengan menggunakan teknik probability sampling, dengan metode stratified random sampling. Analisis data menggunakan Structural Equation Modeling (SEM) berbasis varians, yaitu Partial Least Squares (PLS-SEM), mengingat terdapat variabel dengan indikator reflektif dan formatif di dalam satu model penelitian. Temuan penelitian ini menunjukkan, secara simultan Keterlibatan Orang tua, Dukungan Teman Sebaya, dan Dukungan Guru merupakan prediktor-prediktor signifikan dari Strategi SRL. Selain itu, secara parsial, ketiga exogenous variable (Keterlibatan Orang tua, Dukungan Teman Sebaya, dan Dukungan Guru), masing-masing juga menunjukkan adanya pengaruh signifikan terhadap Strategi SRL. Dukungan Guru memberikan kontribusi yang terbesar, disusul Dukungan Teman Sebaya, dan Keterlibatan Orang tua sebagai kontributor yang paling kecil. Katekis perlu menyadari pentingnya menumbuhkan SRL dalam diri siswa ketika melakukan katekese.